Wind and water erosion of non cultivated sandy soils in the Sahel: a case study in northern Burkina Faso, Africa - Rajot, J.L.; Ribolzi, Olivier; Planchon, O.; Karambiri, H. (2005)
In the Sahel, sandy soils are widespread and support not only most of pearl millet production, the major staple crop in the region, but also forage production for livestock. Parent sediments of these soils have an aeolian origin and hence are prone to wind erosion. However, the clay content, albeit very low, results in the formation of crusts during rainfall, thus leading to runoff and water erosion. Squall lines, major rainfall events of the rainy season, are usually preceded by intense wind. Wind and water erosion is thus closely associated both in time and in space, but they are rarely studied simultaneously. Erosion measurements were carried out during two years (2001, 2002) on a small catchment of grazing land (1.4 ha) at Katchari, Burkina Faso, typical of the Sahel area under 500 mm annual rainfall. Wind erosion occurred at the onset of the rainy season, when soil cover is the lowest, from May to 15th of July, before vegetation growth. Water erosion occurred throughout the rainy season, but some intense events produced most of the total annual erosion. Wind caused the largest sediment fluxes leading to both erosion (up to 20 Mg ha-1 yr-1) and deposits (up to 30 Mg ha-1 yr-1) according to the area of the catchment. Water erosion is one order of magnitude lower than wind erosion, and is more intense where wind erosion is the highest. Thus the same area is eroded both by wind and water. Conversely, in areas where there are aeolian deposits, water erosion is low and these areas correspond to fertile islands where vegetation grows. At this study scale, there is no land degradation, but intense dynamics leading to a high spatial variability typical of the Sahelian environment. On this uncultivated area, the dynamics were similar to those recorded in other Sahelian cultivated millet fields.